Impulse Buying Behavior in TikTok Live Streaming Commerce: An S-O-R Approach to Generation Z Fashion Consumers in Indonesia - Rizki Misbachus Surur; Kholifah Kholifah; Yordan Hermawan Apidana (Journal of Digital Business and Management, 2026)
This study explores the psychological mechanisms behind impulse buying behavior among Generation Z consumers on TikTok Live Streaming Commerce, with a particular focus on fashion products. Using the Stimulus-Organism-Response (S-O-R) framework, the study investigates how six external stimuli streamer attractiveness, trustworthiness, expertise, and product-related attributes such as usefulness, convenience, and price affect internal psychological states, namely perceived usefulness and perceived enjoyment, which in turn influence the urge to buy impulsively. A total of 413 valid responses were collected through purposive sampling and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that perceived enjoyment is the strongest predictor of impulse buying urge, followed by perceived usefulness. Interestingly, perceived usefulness does not significantly influence perceived enjoyment, indicating that emotional engagement in live streaming commerce is shaped more by interactive and affective elements than by rational evaluations. Streamer characteristics such as attractiveness, expertise, and trustworthiness significantly enhance perceived enjoyment, while product usefulness, convenience, and price contribute positively to perceived usefulness. These findings confirm that impulse buying among Gen Z is primarily driven by emotionally charged viewing experiences, rather than utilitarian considerations. The study extends the application of the S-O-R model to real-time social commerce environments, offering theoretical insights into the dual roles of affective and cognitive appraisals, and provides practical implications for businesses aiming to optimize consumer engagement through TikTok Live